2021
DOI: 10.1111/odi.13777
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of oral mucositis in paediatric patients undergoing haematopoietic stem cell transplantation

Abstract: Background A complete understanding of oral mucositis (OM) is crucial to develop appropriate interventions to aid in the successful overall health outcome of paediatric patients undergoing haematopoietic stem cell transplantation (HSCT). Aims This study aimed at determining the prevalence and severity of OM and at identifying the predictive factors that might aggravate OM at one‐week, two‐week and three‐week post‐HSCT. Methods This retrospective, hospital‐based study reviewed the medical records of 170 paediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…This was expected, as the majority of NMD group had been exposed to nonmyeloablative and reduced toxicity conditioning. This finding contrasts with another study focused on children with cancer and primary immunodeficiencies [3], which identified a significantly higher risk of OM in children with immunodeficiencies. Probably the use of laser therapy may have influenced the results of mild OM severity in the NMD group.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This was expected, as the majority of NMD group had been exposed to nonmyeloablative and reduced toxicity conditioning. This finding contrasts with another study focused on children with cancer and primary immunodeficiencies [3], which identified a significantly higher risk of OM in children with immunodeficiencies. Probably the use of laser therapy may have influenced the results of mild OM severity in the NMD group.…”
Section: Discussioncontrasting
confidence: 99%
“…When examining all the patients as a whole, we detected that the incidence of OM in our study (84.8%) was higher than that reported in other pediatric HSCT studies, which ranged from approximately 40.0% to 80.0% [3,4,[15][16][17]. This discrepancy was likely due to the inclusion of cases with mild erythema (classified as grade I by the dental team) in the overall frequency of OM observed in our study.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Their severity can vary from mucosal atrophy, swelling, and mild erythema to severe oral ulcers [ 22 ]. Previous studies have reported OM prevalence ranging 41%–100 % [ 2 , 3 , 13 , 19 , [23] , [24] , [25] ]. To date, consensus lacks on whether periodontal status affects OM incidence.…”
Section: Discussionmentioning
confidence: 99%